2017
DOI: 10.1111/jth.13814
|View full text |Cite
|
Sign up to set email alerts
|

Extended pharmacologic thromboprophylaxis in oncologic liver surgery is safe and effective

Abstract: Background The incidence of venous thromboembolism remains high after liver surgery. Objective To evaluate the safety and efficacy of extended pharmacologic thromboprophylaxis in liver surgery for the prevention of venous thromboembolism (VTE). Patient/Methods From August 2013 to April 2015, 124 patients who underwent liver resection for malignancy were placed on an extended pharmacologic thromboprophylaxis protocol. Intraoperative VTE prophylaxis included Thrombo-Embolic Deterrent hose and sequential comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Other lower-quality studies have provided similar results in urologic oncology surgery, 79 after radical cystectomy for bladder cancer surgery, 80,81 and in liver resection for cancer. 82 In lung cancer surgery, the results of the cohort study by Hachey et al 83 suggested that the application of a revised Caprini risk assessment model could be helpful to select patients who would benefit from extended prophylaxis.…”
Section: Clinical Questionmentioning
confidence: 99%
“…Other lower-quality studies have provided similar results in urologic oncology surgery, 79 after radical cystectomy for bladder cancer surgery, 80,81 and in liver resection for cancer. 82 In lung cancer surgery, the results of the cohort study by Hachey et al 83 suggested that the application of a revised Caprini risk assessment model could be helpful to select patients who would benefit from extended prophylaxis.…”
Section: Clinical Questionmentioning
confidence: 99%
“…16,17 Furthermore, there is mounting evidence supporting its use after bariatric, liver and pancreas surgeries. 18,19 Therefore, it is imperative that consensus guidelines are continually revised to reflect the latest research developments.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite recent meta‐analyses demonstrating its safety and efficacy after abdominopelvic surgery for malignant and benign diseases 16,17 . Furthermore, there is mounting evidence supporting its use after bariatric, liver and pancreas surgeries 18,19 . Therefore, it is imperative that consensus guidelines are continually revised to reflect the latest research developments.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the risk of posttransplant hemorrhage and the lack of evidence of anticoagulant prophylaxis in liver surgery, prophylactic anticoagulant therapy following donation is not routinely performed. Nevertheless, several studies have recently reported the safety and efficacy of pharmacological thromboprophylaxis in liver surgery [13, 14]. A recent study on the risk stratification approaches for VTE prophylaxis based on thrombophilia test results in a large cohort of LDLT donors revealed its necessity and usefulness [15].…”
Section: Discussionmentioning
confidence: 99%